AMMONIA GAS INCREASED INAMBIENT AIR BYINSTALLATION OF SNCR SYSTEM AT HEIDELBERGCEMENT INDIA LIMITED (HCIL), - Singh, Bhim; Kumar, Rajesh (International Journal of Psychosocial Rehabilitation, 2021)
India is the second-largest producer of cement in the world, behind only China. All around India, cement factories may be found. To reduce NOx emissions from Cement Kiln stacks, certain Indian Cement Industries have used SNCR systems Only the reaction temperature range known as the "SNCR temperature window of 870-1090oC" yields optimal SNCR efficiency. A water and molecular nitrogen product is formed when NH3 reacts with NOx. Because ammonia is more likely to escape from the process at temperatures above 700 degrees Celsius and less likely to do so at lower ones, it is oxidised as NOx at higher ones. During loading and unloading of Ammonia tankers and the emission of nonreacted ammonia from cement kiln stacks, ammonia is released into the ambient air. This ammonia gas is raising the nearby environment’s concentration of ambient ammonia